MENTAL HEALTH MATTERS: A DETAILED LOOK AT MENTAL WELL-BEING IN ACADEMIA AND HEALTHCARE - Anas Alhur; Sultan alghamdi; Abdullah Aldawsri; Turki Alotaibi; Saeed Alghamdi; Abdullah Alghamdi; Mohammed Alzahrani; Abdulaziz alghamdi; Saeed Alzahrani; Yousef Alzahrani; Mohannad essa; Hussain Jamal; et al. (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
This paper provides a comprehensive exploration of mental well-being, targeting faculty members within higher education and healthcare professionals. It highlights the critical importance of psychological health across both academia and healthcare sectors, underlining unique and shared stressors ranging from the rigors of scholarly and medical duties to the demands of balancing professional and personal lives. By reviewing existing literature and integrating empirical findings, the paper investigates the prevalent mental health conditions, coping strategies employed, and the pivotal role of institutional support in both settings. The goal is to foster resilience and create supportive environments in these crucial sectors, ultimately enhancing the well-being of educators and healthcare providers alike.